2022
DOI: 10.2138/am-2022-8420
|View full text |Cite
|
Sign up to set email alerts
|

Complexions and stoichiometry of the 60.8°//[100](011) symmetrical tilt grain boundary in Mg2SiO4 forsterite: A combined empirical potential and first-principles study

Abstract: In this work we explore the low-energy complexions of the symmetrical tilt grain boundary (GB) 60.8°//[100](011) in forsterite through molecular dynamics and first principles calculations. Using a conservative sampling, we find six stoichiometric complexions with energies ranging from 0.66 to 1.25 J/m2. We investigate the segregation of MgO vacancy pairs, and find that in most cases it is more favorable for the vacancies to lie within the GBs than in the surrounding crystals, leading to new atomic structures. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Similar subgrain boundaries to the SB sample have been described by Heinemann et al (2005) as arrays of edge dislocations with a periodic spacing of approximately 3 nm and a Burgers vector of [001] (see Figure 4, Heinemann et al, 2005). Further structural descriptions can be found in Adjaoud et al (2012) and Furstoss et al (2022). Schematic illustrations of the sample geometries are presented in Figure 1.…”
Section: Samplesmentioning
confidence: 68%
See 2 more Smart Citations
“…Similar subgrain boundaries to the SB sample have been described by Heinemann et al (2005) as arrays of edge dislocations with a periodic spacing of approximately 3 nm and a Burgers vector of [001] (see Figure 4, Heinemann et al, 2005). Further structural descriptions can be found in Adjaoud et al (2012) and Furstoss et al (2022). Schematic illustrations of the sample geometries are presented in Figure 1.…”
Section: Samplesmentioning
confidence: 68%
“…(2012) and Furstoss et al. (2022). Schematic illustrations of the sample geometries are presented in Figure 1.…”
Section: Methodsmentioning
confidence: 96%
See 1 more Smart Citation
“…107 These crystals possess a centrally symmetric hexagonal lattice arranged in a triangular pattern, similar to monolayer crystals, are asymmetrically arranged, lack inversion centers, and exhibit asymmetric charge density distribution, thereby exhibiting piezoelectric effects. 108 Ma et al reported on the synthesis of molybdenum disulfide nanosheets via a hydrothermal method, which were then utilized in the piezocatalytic reduction process of carbon dioxide. 103 The experiment demonstrated that this material independently completes the entire carbon cycle chain from CO 2 capture to conversion, achieving an ultrahigh purity piezocatalytic CO production rate of 543.1 mmol g À1 h À1 .…”
Section: Piezocatalysis For Carbon Dioxide Reductionmentioning
confidence: 99%